A temperature-resistant and oil-resistant modified graphite plugging agent and its application
By using a composite graphite sealant composed of graphene oxide, carboxyl modified graphene oxide and polyacrylate/graphene oxide, the problem of the reduction of compressive strength of existing oil-based drilling fluid leak plugging materials in high temperature and high oil environments is solved, and efficient sealing and high temperature resistance and high oil performance are achieved.
Patent Information
- Application Number
- CN202211318765.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-10-26
AI Technical Summary
The existing oil-based drilling fluid leak plugging materials have reduced compressive strength in high temperature and high oil environments, poor sealing performance, and insufficient sealing performance for fine cracks.
A composite graphite sealing agent that is resistant to temperature and oil resistance is adopted, and the composition includes graphene oxide, carboxyl modified graphene oxide and polyacrylate/graphene oxide. The mechanical properties of the sealing agent are improved through modification and crosslinking.
It achieves excellent sealing performance and high-temperature and high-pressure stability in high-temperature and high-pressure environments, reduces the filtration loss of drilling fluid, and improves the adhesion of the well wall and the pressure bearing performance of cracks.
Smart Images

Figure BDA0003909494620000101 
Figure BDA0003909494620000111 
Figure BDA0003909494620000112
Abstract
Description
Technical Field
[0001] The invention relates to the field of C098 / 03, and in particular to a temperature-resistant and oil-resistant modified graphite plugging agent and application thereof. Background Art
[0002] In the process of developing oil and gas field production layers, the exploitation of deep shale gas has attracted much attention from researchers. With the increasing complexity of geological conditions, for some hard, brittle and broken formations with prominent layer structures and many fine pores, the invasion of oil-based drilling fluid filtrate will bring many unstable factors to the formation. In addition, the pressure of the passing formation water on the fine pores will also cause the instability of the well wall. Therefore, it is necessary to strengthen the strengthening effect of the oil-based drilling fluid on the well wall. However, the commonly used water-based plugging materials do not expand or bridge to form a network under oil-based conditions. The plugging layer is not dense and has low strength. In addition, under high temperature and oil-based mud environment, the compressive strength of the plugging material is greatly reduced. Therefore, it is necessary to develop a plugging material that can withstand high temperature, high oil, good plugging performance and good compatibility with the drilling fluid system.
[0003] Chinese patent CN106609127A discloses an oil-based drilling fluid plugging material and a preparation method thereof, which comprises an oil-soluble swelling material, a modified fiber, a walnut shell and calcium carbonate. Although the plugging material has good compressive resistance, the walnut shell will be partially carbonized after high-temperature aging, causing the compressive strength of the material to drop sharply after working under high-temperature conditions, thereby reducing the plugging; Chinese patent CN112210354A discloses a plugging agent for oil-based drilling fluid, which comprises coal slag powder, shell slag or clam shell slag, minerals, mineral asphalt and epoxy asphalt. Although the preparation method of the plugging agent is simple and can be prepared on-site for use, its high-temperature and oil resistance and the plugging performance for fine cracks still need to be improved. Summary of the invention
[0004] In order to solve the above technical problems, the present invention first provides a temperature-resistant and oil-resistant composite graphite plugging agent, the components of which include graphene oxide, modified graphene oxide and polymer / graphene oxide.
[0005] Preferably, the modified graphene oxide is graphene oxide modified by at least one of a carboxyl group, an amide group, a sulfonic acid group, a benzenesulfonic acid group, a hydroxyl group, and a silicon-oxygen bond.
[0006] Preferably, the modified graphene oxide is carboxyl-modified graphene oxide.
[0007] Furthermore, the preparation method of the carboxyl-modified graphene oxide is as follows: 0.65-0.78 g of oxidized elastic graphite is dispersed in 100-200 mL of distilled water, ultrasonically treated for 20-40 min, 7.0-7.4 g of inorganic base and 6.2-6.5 g of chloroacetic acid are added, ultrasonicated for 2.5-3.5 h, 80-120 mL of dilute hydrochloric acid with a concentration of 3-5 wt % is added, and the residue is dried after filtering to obtain the carboxyl-modified graphene oxide.
[0008] Furthermore, the inorganic base may be sodium hydroxide or potassium hydroxide.
[0009] Furthermore, the polymer in the polymer / graphene oxide may be one or more of polyesters, polyamides, polymethyl silicone resins, and the like.
[0010] Furthermore, the polymer in the polymer / graphene oxide is polyester, preferably polyacrylate / graphene oxide.
[0011] Furthermore, polyacrylate / graphene oxide is prepared by grafting graphene oxide and acrylate monomers and then polymerizing them.
[0012] Furthermore, the preparation method of the polyacrylate / graphene oxide is:
[0013] Disperse graphene oxide and coupling agent in 98% ethanol, stir for 12-18 hours, filter and take out the residue, and dry it; take out the dried residue and ultrasonicate it in 20-80mL methanol solution for 20-30 minutes, add acrylate monomer in nitrogen atmosphere and low temperature to react for 24-36 hours, raise the temperature to 65-85°C, add initiator and methacrylic acid, then raise the temperature to 90-100°C and react for 20-40 minutes, collect the residue and dry it.
[0014] Furthermore, the weight ratio of the graphene oxide to the acrylate monomer is 1:(20-35).
[0015] Furthermore, the acrylic acid ester monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, and isobornyl methacrylate.
[0016] Preferably, the acrylic acid ester monomers are methyl methacrylate and butyl methacrylate; the molecular chains of both are relatively short, and the formed long polymer chains can be quickly adsorbed on the well wall and form a dense adsorption film layer. When other monomers with relatively long molecular chains are used, due to the excessive length of the polymer molecular chain and the large molecular weight, the entanglement between the molecular chains hinders its rapid migration on the well wall surface, and its three-dimensional curling structure also hinders the adsorption of other components on the well wall, the adsorption strength on the well wall is significantly reduced, and its plugging performance is also reduced; similarly, the total amount of methyl methacrylate and butyl methacrylate is controlled to regulate the molecular chain of the polymer.
[0017] Furthermore, the coupling agent is selected from one or more of aluminates, titanates, and silanes; preferably, it is a silane coupling agent; the silane coupling agent has high molecular chain flexibility, can regulate the degree of cross-linking of the polymer three-dimensional network structure, inhibit the friction resistance between the solid fillers and debris in the drilling fluid and the drill bit caused by the increase in system viscosity, and effectively improve the fluidity and lubricity of the drilling fluid.
[0018] Furthermore, the silane coupling agent is selected from one or more of KH-151, KH-171, KH-172, KH-150, and KH-550, preferably KH550.
[0019] Furthermore, the initiator includes but is not limited to ammonium persulfate, potassium persulfate, benzoyl peroxide, dibenzoyl peroxide, azobisisobutyronitrile, etc.; in some embodiments, the initiator is ammonium persulfate or potassium persulfate.
[0020] Preferably, the weight ratio of the initiator, the acrylate monomer and the methacrylate is (0.3-0.7):(90-120):(1-4).
[0021] Furthermore, the graphene oxide described above is a few-layer graphene oxide. The unique two-dimensional structure of graphene and the relative sliding between layers make it have good elastic deformability, which can be used for plugging cracks under different pressures. However, the present application unexpectedly found that when using a single-layer graphene, the elastic deformation performance of the plugging agent is more excellent, and the friction resistance of its drilling fluid is also smaller. The reason for this is that the resistance of a single-layer graphene is much smaller than that of a multi-layer graphene, and the heat conduction speed is fast and the heat generation is uniform. It can transfer the temperature generated by the internal friction resistance in time and reduce the molecular chain breakage caused by local overheating; compared with multi-layer graphene, its larger relative displacement between layers makes it more adaptable to different cracks, and the mechanical properties of the plugging agent will not be reduced by modifying and cross-linking it.
[0022] Preferably, the graphene oxide is a single-layer graphene oxide, and the single-layer sheet diameter is 0.1-20 μm and the thickness is 0.5-3 nm.
[0023] Preferably, the graphene oxide is a single-layer graphene oxide, and the single-layer sheet diameter is 0.2-10 μm and the thickness is 0.5-2 nm.
[0024] Furthermore, the weight ratio of graphene oxide, modified graphene oxide and polymer / graphene oxide in the plugging agent is (0.5-2):5:(2-5).
[0025] Preferably, when the weight ratio of graphene oxide, modified graphene oxide and polymer / graphene oxide in the plugging agent is (1.1-2):5:(3.2-4.7), the prepared plugging agent has excellent wall-fixing performance and high-temperature and high-pressure plugging performance. The lubricating effect of graphene oxide makes it easier for particles to fill in cracks, but it is not resistant to high temperatures. The adhesion of the plugging agent to the rock wall can be increased by carboxyl modification of graphene oxide, but the formation of some defects in its molecular structure reduces the decline of its wall-fixing performance. The long-chain cross-linked structure of polyacrylate / graphene oxide can improve the wall-fixing performance of the plugging interface protective layer, and the hydrophobicity of the ester group can also reduce the filtration loss of its drilling fluid, but its spatial hindrance inhibits the migration and adhesion of the effective components of the anti-blocking layer to the rock layer, and the addition amount should not be too much.
[0026] Secondly, the present invention also provides the use of the plugging agent in oil-based drilling fluid; the oil-based drilling fluid components include: by total weight, diesel, 25-35% CaCl2 solution, 4-6% emulsifier, 0.5-2% wetting agent, 2-4% organic soil, 2-4% filtration reducer, 1-2% CaO, 1-5% modified graphite plugging agent, and weighting material.
[0027] Furthermore, the oil-water ratio of the oil-based drilling fluid is 60 / 40-85 / 15, the pH is 8.5-10.5, and the density is 1.5-2.0 g / cm 3 (20℃).
[0028] Furthermore, the emulsifier includes but is not limited to a composite of one or more of fatty acids and their derivatives, oleic acid, cyclopentanecarboxamide, calcium cyclopentanecarboxylate, petroleum sulfonate iron, etc., and may be at least one of SRRH-O-EMUL, 15BZ-OPE, BZ-OSE, AEO15, WO-NT, HIEMUL, and HICOAT.
[0029] Furthermore, the wetting agent is at least one of alkyl alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide, lecithin and petroleum sulfonate, alkyl polyethylene glycol ether sulfate sodium salt, etc.
[0030] Furthermore, the fluid loss reducer may be at least one of oxidized asphalt, sulfonated asphalt, modified quaternary ammonium salt, modified humic acid, modified resin, and the like.
[0031] Furthermore, the weighting material is barite and / or limestone.
[0032] Beneficial Effects
[0033] 1. This application can be used in different drilling fluids, has good high temperature resistance, stable pressure bearing performance, excellent crack plugging performance, effectively reduces the filtration loss of drilling fluid, has no effect on the electrical stability of oil-based drilling fluid, and has excellent compatibility.
[0034] 2. This application can form a protective film for the well wall while smoothing the well wall and forming a scaly film, so that the sliding friction on the metal surface between the drill pipe and the casing is converted into sliding friction between graphite flakes, thereby reducing the friction of the drilling fluid and the wear on the surface of the drill pipe and the casing, and has excellent lubricity and friction reduction effects.
[0035] 3. The present application has strong adhesion to the well wall and strong material elasticity. It can not only improve the pressure-bearing performance of cracks that are more affected by pressure, but also effectively fill and enhance tiny pores and cracks, and has high adaptability to cracks. DETAILED DESCRIPTION
[0036] Example
[0037] Example 1
[0038] A temperature-resistant and oil-resistant composite graphite plugging agent comprises graphene oxide, carboxyl-modified graphene oxide and polyacrylate / graphene oxide in a weight ratio of 1.6:5:4.
[0039] The graphene oxide is a single-layer graphene oxide purchased from Shanghai Hanlang New Material Technology Co., Ltd., HL-GO.
[0040] The preparation method of carboxyl-modified graphene oxide is as follows: 0.65 g of oxidized elastic graphite is dispersed in 150 mL of distilled water, ultrasonically treated for 30 minutes, 7.2 g of sodium hydroxide and 6.3 g of chloroacetic acid are added, ultrasonicated for 3.0 hours, 100 mL of 4 wt% dilute hydrochloric acid is added, and after filtering, the filter residue is dried at 60° C. for 48 hours to obtain carboxyl-modified graphene oxide.
[0041] The preparation method of the polyacrylate / graphene oxide is as follows: 5g of graphene oxide and 9.3g of silane coupling agent KH550 are dispersed in 120mL of 98wt.% ethanol, stirred at a speed of 700r / min for 15h, filtered to obtain the filter residue, and dried; the dried filter residue is ultrasonicated in 60mL of methanol solution for 25min, 50g of methyl methacrylate and 100g of butyl methacrylate are added in a nitrogen atmosphere at a low temperature of 2°C to react for 30h, the temperature is raised to 80°C, 0.72g of ammonium persulfate and 4g of methacrylic acid are added, the temperature is raised to 95°C to react for 30min, and the filter residue is collected and dried.
[0042] Example 2
[0043] A temperature-resistant and oil-resistant composite graphite plugging agent comprises graphene oxide, carboxyl-modified graphene oxide and polyacrylate / graphene oxide in a weight ratio of 1.1:5:4.7.
[0044] The graphene oxide is a single-layer graphene oxide purchased from Shanghai Hanlang New Material Technology Co., Ltd., HL-GO.
[0045] The preparation method of carboxyl-modified graphene oxide is as follows: 0.65 g of oxidized elastic graphite is dispersed in 100 mL of distilled water, ultrasonically treated for 20 minutes, 7.0 g of sodium hydroxide and 6.2 g of chloroacetic acid are added, ultrasonicated for 2.5 hours, 80 mL of 3 wt% dilute hydrochloric acid is added, and after filtering, the filter residue is dried at 60° C. for 48 hours to obtain carboxyl-modified graphene oxide.
[0046] The preparation method of the polyacrylate / graphene oxide is as follows: 7g of graphene oxide and 18.2g of silane coupling agent KH550 are dispersed in 100mL of 98wt.% ethanol, stirred at a speed of 500r / min for 18h, filtered to obtain the filter residue, and dried; the dried filter residue is ultrasonicated in 30mL of methanol solution for 20min, 122.5g of methyl methacrylate and 122.5g of butyl methacrylate are added in a nitrogen atmosphere at a low temperature of 2°C to react for 30h, the temperature is raised to 70°C, 1.43g of ammonium persulfate and 3g of methacrylic acid are added, the temperature is raised to 95°C to react for 30min, and the filter residue is collected and dried.
[0047] Example 3
[0048] A temperature-resistant and oil-resistant composite graphite plugging agent comprises graphene oxide, carboxyl-modified graphene oxide and polyacrylate / graphene oxide in a weight ratio of 2:5:3.2.
[0049] The graphene oxide is a single-layer graphene oxide purchased from Shanghai Hanlang New Material Technology Co., Ltd., HL-GO.
[0050] The preparation method of carboxyl-modified graphene oxide is as follows: 0.78 g of oxidized elastic graphite is dispersed in 200 mL of distilled water, ultrasonically treated for 40 min, 7.4 g of sodium hydroxide and 6.5 g of chloroacetic acid are added, ultrasonicated for 3.5 h, 120 mL of 5 wt% dilute hydrochloric acid is added, and after filtering, the filter residue is dried at 60 ° C for 48 h to obtain carboxyl-modified graphene oxide.
[0051] The preparation method of the polyacrylate / graphene oxide is:
[0052] 3 g of graphene oxide and 3.2 g of silane coupling agent KH550 were dispersed in 130 mL of 98 wt.% ethanol, stirred at a speed of 800 r / min for 12 h, filtered to obtain the residue, and dried; the dried residue was ultrasonicated in 80 mL of methanol solution for 30 min, 12 g of methyl methacrylate and 48 g of butyl methacrylate were added in a nitrogen atmosphere at a low temperature of 2° C., and reacted for 36 h, then the temperature was raised to 85° C., 0.45 g of ammonium persulfate and 6 g of methacrylic acid were added, and the temperature was raised to 95° C. and reacted for 30 min, and the residue was collected and dried.
[0053] Comparative Example 1
[0054] The invention is basically the same as Example 1, except that: a temperature-resistant and oil-resistant composite graphite plugging agent, the components of which include graphene oxide and polyacrylate / graphene oxide, with a weight ratio of 1.6:9.
[0055] Comparative Example 2
[0056] Basically the same as Example 1, except that: a temperature-resistant and oil-resistant composite graphite plugging agent, the components include graphene oxide, carboxyl-modified graphene oxide and polyacrylate / graphene oxide, with a weight ratio of 1.6:5:6.
[0057] Comparative Example 3
[0058] The method is basically the same as Example 1, except that the silane coupling agent is KH560.
[0059] Comparative Example 4
[0060] The method is basically the same as Example 1, except that the graphene oxide is purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., XT-C4-06.
[0061] Comparative Example 5
[0062] The method is basically the same as Example 1, except that: the preparation method of the polyacrylate / graphene oxide is as follows: 6 g of graphene oxide and 3.2 g of silane coupling agent KH550 are dispersed in 130 mL of 98 wt.% ethanol, stirred at a speed of 800 r / min for 12 h, filtered to obtain the filter residue, and dried; the dried filter residue is ultrasonicated in 80 mL of methanol solution for 30 min, 30 g of methyl methacrylate and 30 g of lauryl acrylate are added in a nitrogen atmosphere and a low temperature of 2 ° C. After reacting for 36 h, the temperature is raised to 85 ° C., 0.45 g of ammonium persulfate and 6 g of methacrylic acid are added, and the temperature is raised to 95 ° C. After reacting for 30 min, the filter residue is collected and dried.
[0063] The present invention also provides an oil-based drilling fluid prepared by the modified graphite plugging agent of the above embodiment, the components comprising: by total weight, 0# diesel, 30% CaCl2 solution, 5% SRRH-O-EMUL, 1.2% petroleum calcium sulfonate T106, 3% organic soil HW Gel-3, 3% oxidized asphalt DQHA, 1.5% CaO, 3% modified graphite plugging agent, barite; wherein the oil-water ratio is 85 / 15, the pH is 9.5, and the density is 1.8 g / cm 3 (20℃).
[0064] Performance testing method:
[0065] 1. Sand bed plugging experiment: It was carried out in accordance with the standard SY / T5840-2007 indoor test method for bridging plugging materials for drilling fluids; the sand bed was made of 40-60 mesh sand and 60-80 mesh sand mixed and laid flat at a mass ratio of 80:20, the test temperature was 100°C and 120°C, the penetration pressure was 6MPa, and the time was 30min; the test results of the sand bed leakage A are shown in Table 1.
[0066] 2. Crack plugging experiment: The test was carried out in accordance with the standard Q / SH0277-2009 for evaluating the high temperature and high pressure plugging ability of bridging plugging fluids; the test temperature was 200°C, the crack width was 1mm, and the pressure lasted for 30min; the leakage B test results are shown in Table 2.
[0067] 3. Compatibility: The plugging agent in the embodiment was added to the prepared oil-based drilling fluid, and the mixture was hot-rolled at 150°C for 16 hours to measure the rheological properties; the HTHP experimental temperature was 150°C and the pressure was 3.5 MPa; the test temperature was 50°C, and the test results are shown in Table 3.
[0068] Performance test results:
[0069] Table 1
[0070]
[0071]
[0072] Table 2
[0073] Sample No. Loss mL Compression strength MPa Leakage plugging situation Example 1 38 8 Capable of blocking Example 2 45 7 Capable of blocking Example 3 42 7 Capable of blocking Comparative Example 1 370 5 Can block Comparative Example 2 190 6 Can block Comparative Example 3 86 7 Can block Comparative Example 4 295 6 Can block Comparative Example 5 160 6 Can block
[0074] Table 3
[0075]
[0076]
Claims
1. A temperature-resistant and oil-resistant composite graphite plugging agent, characterized in that: The components include graphene oxide, modified graphene oxide and polymer / graphene oxide; The modified graphene oxide is graphene oxide modified by carboxyl groups; The polymer / graphene oxide is polyacrylate / graphene oxide; the preparation method of the polyacrylate / graphene oxide is: dispersing graphene oxide and a coupling agent in 98% ethanol, stirring for 12-18 hours, filtering to obtain a filter residue, and drying; taking the dried filter residue and ultrasonicating it in 20-80mL of a methanol solution for 20-30 minutes, adding an acrylate monomer in a nitrogen atmosphere at a low temperature of 2°C to react for 24-36 hours, raising the temperature to 65-85°C, adding an initiator and methacrylic acid, and then raising the temperature to 90-100°C to react for 20-40 minutes, collecting the filter residue and drying it; the coupling agent is selected from one or more of KH-151, KH-171, KH-172, KH-150, and KH-550; the polyacrylate / graphene oxide is formed by grafting graphene oxide and an acrylate monomer and then polymerizing them, and the weight ratio of the two is 1:(20-35); The acrylic acid ester monomers are methyl methacrylate and butyl methacrylate; The graphene oxide is a few-layer graphene oxide; The weight ratio of graphene oxide, modified graphene oxide and polymer / graphene oxide in the plugging agent is (0.5-2):5:(2-5).
2. Use of the temperature-resistant and oil-resistant composite graphite plugging agent according to claim 1 in oil-based drilling fluid.
3. The use of the temperature-resistant and oil-resistant composite graphite plugging agent in oil-based drilling fluid according to claim 1, characterized in that: The oil-based drilling fluid components include: by total weight, diesel, 25-35% CaCl2 solution, 4-6% emulsifier, 0.5-2% wetting agent, 2-4% organic soil, 2-4% fluid loss reducer, 1-2% CaO, 1-5% composite graphite plugging agent, and weighting material.
4. The use of the temperature-resistant and oil-resistant composite graphite plugging agent in oil-based drilling fluid according to claim 3, characterized in that: The oil-water ratio of the oil-based drilling fluid is 60 / 40-85 / 15, and the pH value is 8.5-10.5.
Citation Information
Patent Citations
Oil-based drilling fluid plugging material and preparation method thereof
CN106609127A
Plugging agent for oil-based drilling fluid
CN112210354A
Polyacrylate grafted graphene oxide plugging agent and oil-based drilling fluid
CN114752365A